Community Leadership Practices in Neighborhood Association: Roles, Challenges, and Social Cohesion in Indonesia - Heri Subowo (LifeSciFi, 2026)
This study explores community-based leadership within neighborhood associations in Indonesia, where grassroots governance leaders serve as key intermediaries between citizens and formal government institutions despite being under-theorized in public administration literature. The study aims to examine how neighborhood association leaders perceive and perform their roles, address challenges, and foster social cohesion. Using a qualitative approach, the research draws on 90 in-depth interviews with neighborhood association leaders across diverse urban and rural regions in Indonesia and applies thematic analysis to identify recurring leadership values and community practices. Findings reveal that neighborhood association leadership is shaped by moral commitment, voluntary service, and social trust rather than formal authority or material incentive. The principal results underscore five core dimensions: mediating state-citizen relations, maintaining neighborhood harmony, fostering participatory governance, navigating informal constraints, and initiating micro-level innovations. These dimensions reflect a hybrid leadership model that blends administrative tasks with cultural stewardship and relational ethics. The paper concludes that neighborhood association leaders exemplify a form of community-based leadership deeply rooted in local values and collective responsibility. Their practices deepen understanding of informal leadership and everyday governance, offering insights for decentralization policy, civic engagement, and community leadership development.